Potencial do óleo de Aloysia citriodora Palau no controle de fitopatógenos e na indução de resistência ao tombamento de plântulas de feijão, pepino e beterraba - Freddo, Álvaro Rodrigo (2015)
The crops are affected by pests and diseases that decrease productivity. Among them are the damping off of seedlings that can occur in pre and post-emergence. In bean crops, cucumber and beet these diseases occur, being caused by various pathogens, especialy fitopathogenic fungi. Several measures are used for the controle of such diseases, among them, is the chemical seed treatment fungicides. However, society has become increasingly concerned about the quality and food and environmental contamination, generation a growting search for sensitive products to humans and the environment. The use of essential oils to control plant pathogens is an example of alternative tested by science in the search for less aggressive technologies. This study aimed to evaluate the efficiency of the use of essential oil Aloysia citriodora, in control of pathogens causing damping off in beans, cucumber and beet. This thesis was divided in four chapters, the introductory first, and the other addressing the control of Pythium sp. in beans, Sclerotinia sclerotiorum on cucumber, and Fusarium sp. on beet. The methodology consisted of four experiments in each pathosystem, with all the work done at the Federal Technological University of Parana, Campus Dois Vizinhos. In the first experiment evaluated the fungistatic and fungicidal effect of the essential oil of A. citriodora on PDA in vitro in mycelial growth of pathogens studied. In the second experiment evaluated the in vitro effect of essential oil concentrations of A. citriodora in BD medium on microscope slides, on the germination of sporangia Pythium sp. and conidia Fusarium sp., and in Petri dishes with PDA medium, the sclerotia germination speed index of S. sclerotiorum. In the third experiment, we evaluated in germination test in paper roll (PR), the phytotoxic effect or not the use of essential oil concentrations of A. citriodora in dry bean seed, cucumber and beet. The variables used to assess this experiment were the germination percentage, mediun green mass per plant and average length of seedlings. In the fourth experiment we assessed the effect of treating bean seeds, cucumber and beet with essential oil contents of A. citriodora, seeds in their subsequent substrates contamined with pathogens studied, Pythium sp., S. sclerotiorum and Fusarium sp. In this experiment we used the following variables: percentage of emergence, percentage of post-emergence damping off, green average mass per plant, average length per plant and biochemical analyzes. The biochemistry of plant tissues evaluated were as follows: protein content, enzymatic activities of peroxidases, phenylalanine ammonia-liase (PAL), chitinases and β-1,3-glucanases. The in vitro results show that the essential oil has fungistatic and fungicidal effect on mycelial growth, on sporangia germination, conidia and sclerotia of the pathogens studied in this work, wich may be related to its major components, citral and limonene. The oil also exhibits low phytotoxicity to seeds of the species studied, only in beans decreases germination in most studied dosage (0,25%), cucumber also in the higher dosage (0,25%) reduce the length of seedlings, and beet there were no negative effects to the seedlings. In the test in substrate contaminated with the pathogens, the use of essential oil: increased germination and decreased post emergence damping off of beans seedlings; at a concentration of 0,0625% decreases post emergence damping off in cucumber. In biochemical analyzes found an increase in the enzymatic activity of peroxidases and β-1,3-glucanases on beans, and glucanases on cucumber, and increased enzyme activity of peroxidases on beet, showing action in resistance induction at damping off.